The Revelation of Martin of Tours. Nero and the Antichrist as starring of Doomsday - Cuesta Fernández, Jorge (ARYS. Antigüedad: Religiones y Sociedades, 2019)
Judaism and Christianity have left writings belonging to the apocalyptic genre, interesting for the knowledge of ideas about the end of the world and especially of future expectations that Jews and Christians housed in the most critical moments of their existence. However, the themes and motifs of the examples of this genre features found in other writings that could not be classified as “apocalypse”. The text of Sulpicius Severus about apocalyptic thought of Martin of Tours has become the subject of debate for the many literary examples that elevate Nero an eschatological category and associated with the Antichrist. This paper compares the content of the ideas of Martin with other texts such content to show whether the ideas of Martin can be defined as either reuse or by their originality.
Keywords: Nero; Antichrist; Apocalypse; apocalyptic genre; Belial; Sulpicius Severus; Martin of Tours; Nero Redivivus